Combining environmental niche models, multi‐grain analyses, and species traits identifies pervasive effects of land use on butterfly biodiversity across Italy. Issue 7 (5th February 2023) - Riva, Federico; Barbero, Francesca; Balletto, Emilio; Bonelli, Simona
Abstract: Understanding how species respond to human activities is paramount to ecology and conservation science, one outstanding question being how large‐scale patterns in land use affect biodiversity. To facilitate answering this question, we propose a novel analytical framework that combines environmental niche models, multi‐grain analyses, and species traits. We illustrate the framework capitalizing on the most extensive dataset compiled to date for the butterflies of Italy (106, 514 observations for 288 species), assessing how agriculture and urbanization have affected biodiversity of these taxa from landscape to regional scales (3–48 km grains) across the country while accounting for its steep climatic gradients. Multiple lines of evidence suggest pervasive and scale‐dependent effects of land use on butterflies in Italy. While land use explained patterns in species richness primarily at grains ≤12 km, idiosyncratic responses in species highlighted "winners" and "losers" across human‐dominated regions. Detrimental effects of agriculture and urbanization emerged from landscape (3‐km grain) to regional (48‐km grain) scales, disproportionally affecting small butterflies and butterflies with a short flight curve. Human activities have therefore reorganized the biogeography of Italian butterflies, filtering out species with poor dispersal capacity and narrow niche breadth not only from local assemblages, but also from regional species pools. These results suggest that global conservation efforts neglecting large‐scale patterns in land use risk falling short of their goals, even for taxa typically assumed to persist in small natural areas (e.g., invertebrates). Our study also confirms that consideration of spatial scales will be crucial to implementing effective conservation actions in the Post‐2020 Global Biodiversity Framework. In this context, applications of the proposed analytical framework have broad potential to identify which mechanisms underlie biodiversity change at different spatial scales. Abstract : We propose a novel analytical framework that leverages big biodiversity data, environmental niche models, and species traits to assess how environmental gradients influence biodiversity across spatial scales. Implementing the framework, we found that agriculture and urbanization have affected butterfly biogeography in Italy from local to regional scales, disproportionately affecting small species and species with a short flight period. We discuss the importance of considering large‐scale land use patterns for biodiversity conservation in the Post‐2020 Global Biodiversity Framework and, more broadly, how the proposed analytical framework can aid in this direction. Abstract : Comprendere come le specie rispondono alle attività umane è essenziale per la conservazione della biodiversità. Tuttavia, in questo ambito, rimane poco chiaro il ruolo dei cambiamenti dell'uso del suolo su larga scala. Per contribuire a colmare queste lacune, proponiamo un nuovo approccio analitico che combina modelli di nicchia ambientale, analisi su diverse scale spaziali e tratti funzionali delle specie indagate. Testiamo questo approccio con un dataset inedito di distribuzione delle farfalle italiane (106.514 osservazioni per 288 specie), valutando l'effetto di agricoltura e urbanizzazione sulla diversità delle farfalle a scale crescenti, da locali a regionali (i.e., da 3 a 48 km "grains"). I nostri risultati suggeriscono che le attività umane hanno avuto effetti diffusi e dipendenti dalla scala di analisi sulla composizione delle comunità di farfalle italiane. Mentre l'uso del suolo spiega la ricchezza specifica principalmente a scale ≤ 12 km, risposte idiosincratiche evidenziano specie "vincenti" e "perdenti" nelle aree dominate dall'uomo anche a scale più ampie. Effetti negativi dell'agricoltura e dell'urbanizzazione emergono fino a scale regionali (48 km) e incidono principalmente su farfalle di piccole dimensioni e con periodo di volo breve. Le attività umane hanno quindi rimaneggiato la biogeografia delle farfalle italiane, causando la perdita di specie sensibili non solo dalle comunità locali, ma anche da intere regioni. Il nostro lavoro dimostra che gli sforzi impiegati nella conservazione della biodiversità devono considerare i pattern nell'uso del suolo su larga scala, anche per organismi che spesso si presume persistano in piccole aree naturali (come molti invertebrati). Considerare le scale spaziali sarà perciò cruciale nel progettare azioni di conservazione che siano efficaci per raggiungere gli obiettivi di iniziative come la Strategia della Biodiversità 2030. In tale contesto, l'approccio analitico dimostrato in questo studio si propone come strumento metodologico per identificare i meccanismi alla base del cambiamento della biodiversità a diverse scale spaziali.